THE CHARACTERISTIC OF TRAHEAN SWAMPLAND IN SOUTH TEWEH REGENCY OF NORTH BARITO CENTRAL KALIMANTAN - Irawati Citra Dewi (Jurnal Teknologi Berkelanjutan, 2015)
The wet Trahean swampland is known as a farming and fishing area for the residents of Trahean village. Trahean swamp covers 1,500 ha, comprising 70.16 ha of farming area, 8 ha of fishing area and other public facility areas of 1411.84 ha. Trahean swampland is water sustainable all year long. Despite long dry season, the Trahean village rarely experiences severe drought. The water source of Trahean village is from rainfall and river branch from Barito River that flows to the farming area. This research aims to identify the characteristic of the swampland so that it can be used as a farming area. The soil type in this area is Aluvial swamp.This research was conducted by collecting primary and secondary data. The assessment of land suitability shows that Trahean swamp has a limiting factor. This limiting factor affects its productivity and thus, this area needs more input. The limits are usually caused by the farmers themselves.Based on the land suitability class result, the Trahean swampland is categorized into S1 and S2 land suitability, where the dominant land suitability is S2. Based on the physical and chemical conditions, the Trahean swampland is suitable for farming.